Evaluation of the motor function of patients with renal failure undergoing hemodialysis: a cross-sectional study - Souza, Felipe Heylan Nogueira de; Pessoa, Raynara Maritsa Cavalcante; Filho, Edson Meneses da Silva; Cezarino, Leandro Gonçalves; Chagas, Nadla di Karlla; Pereira, Rodrigues Ramos; Ferreira, Pamela de Sousa; Cacho, Ênio Walker Azevedo (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Chronic Kidney Disease (CKD) is becoming a public health problem, due its chronic, progressive and irreversible kidney function. Objective: To evaluate the motor function of patients with CKD undergoing hemodialysis (HD) treatment. Method: a cross‑sectional study carried out at João XXIII hospital in the city of Campina Grande-Brazil, from August to September 2016. Inclusion criteria were: subjects aged between 20 and 60 years old of both gender and who were undergoing HD treatment for more than 1 year. Those who presented cognitive and visual impairment, amputees, history of stroke or traumatic brain injury and underwent surgical procedure in the 6 months prior to the approach were excluded. Motor function assessment was performed by Motor Function Measurement Scale, which is divided into three dimensions: Dimension 1 (D1): standing position and transfers; Dimension 2 (D2): axial and proximal motor function; Dimension 3 (D3): distal motor function. To evaluate the muscular strength was used the Oxford scale and for the range of motion a goniometer was used. Results: The sample consisted of 20 patients. The correlation between D1 and D2 showed a significant positive association. Significant positive correlation was also observed on the strength of the lower limbs and D1 for all muscle evaluated. On the other hand, the strength of the upper limbs, relative to D2 and D3 showed a moderate positive correlation only between the flexors of the right shoulder and D2. Right elbow flexion was the only variable that presented a negative and moderate correlation with hemodialysis time. Conclusion: The strength and range of motion of the sample were lower than expected for people without pathology, in addition the evaluation methods present in this study were not sensitive to detect any dysfunction.